Teaching inclusive religious education impartially: an English perspective - Jackson, Robert (British journal of religious education, 2017)
The article draws on experience of teaching, teacher education and qualitative research related to an impartial approach to inclusive religious education (including pupils from families who identify with or do not identify with religion or belief groups), in publicly funded schools in England. Such religious education is considered to be intrinsically worthwhile and instrumentally important in contributing to pupils’ personal and social development. The approach considered is hermeneutical, bringing reliable information into relationship with knowledge and experience of pupils and teacher through active learning, including dialogue. Qualitative research on student and early career teachers suggests that appropriate skills and attitudes supporting an impartial approach can be developed, facilitating a relationship of trust between teacher and students. A condition is the development of teachers’ knowledge and understanding of the stances of pupils in their classes. However, some student teachers or teachers with very firmly held views find it very difficult to adopt an impartial approach. On the basis of examples from qualitative research, it is argued that good quality teacher education can assist in developing appropriate skills and attitudes for those wishing to take an impartial approach. Further research, ideally involving partnership between researchers and practitioners, is recommended.